Frugivorous flies and their parasitoids associated with native fruits in an urban area - Coelho, João Batista; Araújo, Edineia da Silva; Silva, Luciana Barboza; Strikis, Pedro Carlos; Zucchi, Roberto Antonio; Lopes, Gleidyane Novais (Semina: Ciências Agrárias, 2020)
This study aimed to know the species of frugivorous flies (Tephritidae and Lonchaeidae) and their parasitoids associated with fruits in home orchards. It was conducted in the Gurgueia Valley, municipality of Bom Jesus, Piauí, Brazil. Fruit collection was carried out from April to December 2016. A total of 959 fruits (12 kg) belonging to seven fruit species were sampled, such as acerola (Malpighia glabra), carambola (Averrhoa carambola), lime (Citrus aurantifolia), balsam pear (Momordica charantia), cherry of the Rio Grande (Eugenia involucrata), umbu-cajá (Spondias bahiensis), and purple mombin (Spondias purpurea). Only three among these species (acerola, umbu-cajá, and purple mombin) were host, with 2,770 frugivorous flies. Umbu-cajá hosted 316 specimens of Anastrepha obliqua, from which puparia have emerged 84 specimens of Opius bellus and four of Pachycrepoideus vindemmiae. Purple mombin hosted Ceratitis capitata (2,384 specimens), Neosilba pendula (69 specimens), and Anastrepha sp. (one male). Eleven specimens of Tetrastichus giffardianus emerged from the puparia of C. capitata. Acerola hosted only one female of C. capitata and six specimens of N. pendula. Ceratitis capitata and N. pendula were recorded for the first-time infesting fruits of purple mombin in Piauí. Tetrastichus giffardianus parasitizing C. capitata in purple mombin was first recorded in the state of Piauí. Pachycrepoideus vindemmiae is a new record in A. obliqua in umbu-cajá in Brazil.